Kemampuan Berpikir Logis Mahasiswa dengan Menggunakan Model Pembelajaran M-APOS - Dwi Maulida Sari; Diyah Hoiriyah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This article aims to analyze students' mathematical logical thinking skills who apply the M-APOS learning model. The research was conducted in the sixth semester at one of the universities in Padangsidimpuan. It was found that the average n-gain of M-APOS class students' logical thinking skills increased in the high category as stated by Hake's criteria for increasing n-gain. The standard deviation value for the M-APOS class shows that the distribution of the n-gain value data is very diverse. This shows that the M-APOS learning model can be used as a learning model that can improve logical thinking skills.